A Novel Chromone Derivative with Anti-Inflammatory Property via Inhibition of ROS-Dependent Activation of TRAF6-ASK1-p38 Pathway - Liu, Hailiang; Xu, Rui; Feng, Lili; Guo, Wenjie; Cao, Ning; Qian, Cheng; Teng, Peng; Wang, Lu; Wu, Xuefeng; Sun, Yang; Li, Jianxin; Shen, Yan; et al. (PLOS ONE, 2012)
The p38 MAPK signaling pathway plays a pivotal role in inflammation. Targeting p38 MAPK may be a potential strategy for the treatment of inflammatory diseases. In the present study, we show that a novel chromone derivative, DCO-6, significantly reduced lipopolysaccharide (LPS)-induced production of nitric oxide, IL-1β and IL-6, decreased the levels of iNOS, IL-1β and IL-6 mRNA expression in both RAW264.7 cells and mouse primary peritoneal macrophages, and inhibited LPS-induced activation of p38 MAPK but not of JNK, ERK. Moreover, DCO-6 specifically inhibited TLR4-dependent p38 activation without directly inhibiting its kinase activity. LPS-induced production of intracellular reactive oxygen species (ROS) was remarkably impaired by DCO-6, which disrupted the formation of the TRAF6-ASK1 complex. Administering DCO-6 significantly protected mice from LPS-induced septic shock in parallel with the inhibition of p38 activation and ROS production. Our results indicate that DCO-6 showed anti-inflammatory properties through inhibition of ROS-dependent activation of TRAF6-ASK1-p38 pathway. Blockade of the upstream events required for p38 MAPK action by DCO-6 may provide a new therapeutic option in the treatment of inflammatory diseases.